Where, When, and how Long: Factors that Influence the Redemption of Mobile Phone Coupons - Danaher, Peter J.; Smith, Michael S.; Ranasinghe, Kulan; Danaher, Tracey S. (Journal of Marketing Research, 2015)
The use of coupons delivered by mobile phone, so-called “m-coupons,” is growing rapidly. In this study, the authors analyze consumer response to m-coupons for a two-year trial at a large shopping mall. Approximately 8,500 people were recruited to a panel and received three text-message m-coupons whenever they “swiped” their mobile phone at the mall entrances, with downstream redemption recorded. Almost 144,000 m-coupons were delivered during the trial, representing 38 stores that supplied 134 different coupons. The authors find that an important feature of m-coupons is where and when they are delivered, with location and time of delivery significantly influencing redemption. How long the m-coupons are valid (expiry length) is also important because redemption times for m-coupons are much shorter than for traditional coupons. This finding suggests that their expiration length should be shortened to help signal time urgency. Nevertheless, traditional coupon features, such as face value, still dominate m-coupon effectiveness, as does the product type, with snack food coupons being particularly effective.